Chromothripsis with at least 12 breaks at 1p36.33-p35.3 in a boy with multiple congenital anomalies - Gamba, Bruno Faulin; Richieri-Costa, Antônio; Costa, Silvia; Rosenberg, Carla; Ribeiro-Bicudo, Lucilene Arilho (Springer Nature, 2015)
Terminal deletion in the short arm of chromosome 1 results in a disorder described as 1p36 deletion syndrome. The resulting phenotype varies among patients including mental retardation, developmental delay, sensorineural hearing loss, seizures, heart defects, and distinct facies. In the present case, we performed array-comparative genomic hybridization in a boy with multiple congenital malformations presenting some features overlapping the 1p36 deletion phenotype for whom chromosomal analysis did not reveal a terminal deletion in 1p. Results showed complex chromosome rearrangements involving the 1p36.33-p35.3 region. While the mechanism of origin of these rearrangements is still unclear, chromothripsis—a single catastrophic event leading to shattering chromosomes or chromosome regions and rejoining of the segments—has been described to occur in a fraction of cancers. The presence of at least 12 clustered breaks at 1p and apparent lack of mosaicism in the present case suggests that a single event like chromothripsis occurred. This finding suggests that chromothripsis is responsible for some constitutive complex chromosome rearrangements.
Keywords: Array-CGH; Chromothripsis; Complex chromosomal rearrangement; Multiple congenital anomalies